miR-4698-Trim59 axis plays a suppressive role in hepatocellular carcinoma - Xu, Chunquan (Frontiers in bioscience, 2020)
microRNAs (miRNAs) are important players in tumor suppression and oncogenesis. In this study, we aimed to explore the role of miR-4698 with its potential target tripartite motif-containing 59 (Trim59), a protein with oncogenic function, in hepatocellular carcinoma (HCC). The expression of miR-4698 was significantly lower in HCC tissues and HCC cell lines compared to normal tissues adjacent to tumors and in normal hepatic cell lines. Overexpression of miR-4698 in HCC cells by transfection of its mimic significantly inhibited cell proliferation, migration, invasion and epithelial-mesenchymal transition (EMT), whereas its antisense oligonucleotides (ASOs) exerted the opposite effect. Trim59 was identified as a target of miR-4698 in miRDB, and consistent with this prediction, the expression of Trim59 was inversely correlated with that of miR-4698 in HCC, and miR-4698 overexpression led to a significant decrease in the luciferase activity of pRL-Trim59-3'-UTR but not mutant pRL-Trim59-3'-UTR. Moreover, the miR-4698 mimic inhibited the expression of Trim59. Overexpression of Trim59 abrogated the inhibitory effects of miR-4698. In conclusion, these data show that the miR-4698-Trim59 axis plays a tumor-suppressive role in HCC.